Penggunaan Aplikasi Geschool Pada Pembelajaran Bernyanyi Secara Polifoni Di SMP Negeri 25 Padang - Dian Alfianita Zendrato; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2021)
The research problem was motivated by the obstacles faced by students in online learning. At SMP Negeri 25 Padang, the obstacles are in the form of internet quotas, signals, and difficulty level in accessing application so that the online learning is disrupted. This study aims to find out and describe the use of the Geschool application in learning polyphony singing of Culture and Arts subject matter in class VII, SMP Negeri 25 Padang.This study belongs to a descriptive qualitative research. The object of this research was the seventh grade students at SMP Negeri 25 Padang. This study used stationery and mobile phone as research instruments. The data were in the form of primary and secondary data collected by using literature study, observation, interviews, and documentation. The data were analyzed by using 6 stages consisting of identifying, classifying, clarifying, describing, analyzing, and concluding the data. Based on the results of the study, it can be concluded that the use of Geschool application in learning polyphonic singing has been going well in the distrIbution of materials and assignments. It is suitable with the features provided by the Geschool application. However, it does not work well for practical learning. This is due to the fact that the practical learning is not optimal if it is taught through video learning only.